Analisis Kesalahan Mahasiswa Prodi Teknik Informatika Kelas A Universitas Pahlawan Tuanku Tambusai Pada Mata Kuliah Kalkulus 1 - Zulfah Zulfah (Universitas Pahlawan Tuanku Tambusai, 2018)
This study aims to analyze error in accordance with mathematical objects done by students in the course of Calculus I. One of the material calculus 1 studied is the material functions, ranging from function definition to trigonometric function. The function material is a pre-paid material before studying derivative material which will also be studied in Calculus 1 and 2. The research method used is descriptive qualitative method, and quantitative descriptive. Qualitative description that describes the mistakes made learners by using words, while descriptive quantitative describes the amount of mistakes made learners on each mathematical object by using numbers. Data collection techniques used in this study is the test method. So the instrument used to collect data is essay test. Based on the results of the analysis it can be concluded that the errors are most often done is a mistake of principles and concepts, and followed procedural errors. This error can be reduced by doing a lot of practice doing the questions on Calculus 1 book